FAKTOR REDUKSI ARUS GANGGUAN PADA KABEL 150 KV FASA TIGA BERINTI TUNGGAL - Rinna Hariyati; Retno Aita Diantari; Abi Cristian (Sekolah Tinggi Teknik - PLN, 2015)
In urban areas the use of underground cables is growing rapily in recent. Cable line are used to distribute electrical energy is called high voltage cable line. When a ground fault occurs in a power network, a ground fault current flow towards the sources through the earth and the other flow through mettalic sheath of the cable. For safety in substation reduction factor must be small. In this paper present the method for calculate reduction factor value at three single core cable. This method can give the value of reduction factor for different distance and different ground fault locations,happened between source substation and suplied substation.